2011
DOI: 10.1111/j.1600-079x.2011.00901.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of osteoporosis in adolescent idiopathic scoliosis: experimental scoliosis in pinealectomized chickens

Abstract: To clarify the mechanism of osteoporosis in adolescent idiopathic scoliosis (AIS), we investigated radiological and histological changes in the cervical vertebrae of a chicken thoracic scoliosis model. Forty newly hatched broiler chicks were randomly divided into four equal groups: sham-operated chickens serving as control (CON), pinealectomized chickens (PNX), sham-operated (CON + MLT) and pinealectomized chickens (PNX + MLT) that received intraperitoneal administration of melatonin. Pinealectomy was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
(80 reference statements)
0
27
0
2
Order By: Relevance
“…The number of osteoblasts was significantly decreased as a result of pineal loss, while the number of osteoclasts showed no significant difference among chickens. These results suggest that melatonin deficiency reduces osteoblast proliferation and leads to the development of osteoporosis . Chen et al found that treatment with 50 nmol/L melatonin enhanced the mRNA expression levels of osteogenic marker genes, including ALP, osteopontin, osteocalcin, and RUNX2, in the normal control hMSC group compared with the untreated normal control.…”
Section: Prospects and Conclusionmentioning
confidence: 93%
“…The number of osteoblasts was significantly decreased as a result of pineal loss, while the number of osteoclasts showed no significant difference among chickens. These results suggest that melatonin deficiency reduces osteoblast proliferation and leads to the development of osteoporosis . Chen et al found that treatment with 50 nmol/L melatonin enhanced the mRNA expression levels of osteogenic marker genes, including ALP, osteopontin, osteocalcin, and RUNX2, in the normal control hMSC group compared with the untreated normal control.…”
Section: Prospects and Conclusionmentioning
confidence: 93%
“…In keeping with this, a disruption in melatonin‐mediated signaling, whether it be through a suppression of nocturnal melatonin levels by light at night (LAN) or through impaired melatonin receptor signaling in osteoblasts, is thought to underlie, respectively, the increased risk of hip and wrist fracture and low BMD in shift workers and to the development of adolescent idiopathic scoliosis . Decreases in melatonin have been shown to alter bone morphology in various models including fish , chickens , and mice . In rodents and sheep, LAN or removal of the melatonin source through pinealectomy increases bone marker turnover and decreases bone mass .…”
Section: Melatonin and Bonementioning
confidence: 99%
“…Decreases in melatonin have been shown to alter bone morphology in various models including fish , chickens , and mice . In rodents and sheep, LAN or removal of the melatonin source through pinealectomy increases bone marker turnover and decreases bone mass . A restoration of the melatonin peak at night by limiting LAN or by supplementing nighttime levels with exogenous melatonin may prove to be of benefit .…”
Section: Melatonin and Bonementioning
confidence: 99%
“…Also, in children with Smith-Magenis syndrome, a genetic condition associated with bone abnormalities, perturbations in both their sleep and melatonin rhythms exist [6,7]. In rodents, reduction in nocturnal melatonin levels either by light at night (LAN) or by pinealectomy increases bone marker turnover [8,9] and adversely affects their bone health [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%